INCREASING STUDENTS' LEARNING INTEREST AND ACHIEVEMENT USING THE PROBLEM-BASED LEARNING MODEL ASSISTED WITH TRAVEL MAP MEDIA - Lorensa, Luthfia Ayu; Gunawan, Gunawan; Sadeli, Elly Hasan; Kusuma, Jaka Wijaya; Herawati, Rafika Asri (Yayasan Education and Social Center, 2024)
The study aims to determine the increase in interest and achievement in learning through the problem-based learning learning model with the help of an online quiz, namely travel map. This study used a collaborative classroom action research approach. The subject of this study was a grade V student of SD Negeri 1 Dawuhan Kulon. The data collection techniques used in this study were tests in the form of online evaluation questions and non-tests in the form of documentation and observation. The results of the research findings prove that learning using the problem-based learning model using the travel map quiz can increase cognitive learning achievement and student learning interest. The value of learning evaluation before being subjected to class action results are still very poor, namely the class score of 61.4. The application of the Problem-based learning model using the Travel Map Quiz can improve student achievement. This is evident from the average result of cycle I of 70 and the average cycle II of 77.8. The results of interest in learning before learning are still less at 52%. After applying the problem-based learning model using the travel map quiz, it can increase student interest in learning, namely in the first cycle by 70%, including in the sufficient category. Cycle II, the average interest in learning students reached 70.6%, including the good category